Ջերմատնային լոլիկի բույսերում ակտարայի թունազերծման առանձնահատկությունները - Աճեմյան, Լևոն; Միրզոյան, Վարսիկ; Պետրոսյան, Նելլի; Կարապետյան, Գաբրիել (ՀԱԱՀ հիմնադրամ)
Исследованиями установлено, что при внесении Актары в тепличных условиях внекорневым и корневым способами детоксикация препарата в плодах и листьях томата при каждом из этих способов протекает по-разному. В течение срока ожидания (3 дня после применения) остатки пестицида в плодах томата в обоих вариантах не превышали максимально допустимого уровня (МДУ). Однако на 5-й день после внесения через корневую систему наблюдалось увеличение остаточного количества этого ядохимиката как в листьях, так и в плодах. Независимо от способов применения, Актара не оказала существенного влияния на основные качественные показатели плодов томата. The residual behavior of actara in the leaves and fruits of greenhouse tomato plants applied by foliar spraying and drip irrigation method (insectigation) have been studied. The experiments were carried out on the small-grain tomato “Svetil F” hybrid plants under greenhouse conditions in the Republic of Armenia. One part of the plants was sprayed with actara solution (0.6 kg/ha), and the other part was treated with actara through the root system by insectigation method (0.8 kg/ha). For analysis, leaf and fruit samples (>2 kg) were taken 1, 3, and 5 days after the application. It has been found that the detoxification of actara in the fruits and leaves of tomato plants proceeds in different ways depending on the specifics of the application. At the “preharvest interval” (PHI, 3 days after the application), residues of actara in tomato fruits were at the maximum residue level (MRL) in both variants. However, on the 5th day of insectigation, as a result of hysteresis effect an increase of the actara content residues in the leaves and fruits took place. The obtained data did not reveal statistically significant effect of actara on the main quality indicators of tomato fruits, regardless of the method of pesticide application.
Keywords: Ագրոնոմիա